Academic Publishing and «Predatory» Journals - Strielkowski, W.; Gryshova, I. (Наука та інновації, 2018)
Introduction. Publications in prestigious academic journals have a significant impact on the institutional rankings and help researchers to get grants. Problem Statement. Nevertheless, the issue of «where» to publish became more important than «what» to publish. The academic race for the higher number of publications led to debates about the phenomenon of the so-called «predatory» journals that publish scientific «rubbish» for money without proper peer review. Purpose. The purpose is to reveal the essence of «predatory» journals and to prove the necessity of indexation as an effective tool for assessing the quality of scientific publications. Materials and Methods. The ratings of scientific journals and publications in academic journals and «predatory» journals have been compared. Results. The Czech Republic is one of the countries that seem to be particularly obsessed with the issue of «predatory» journals making a storm in a teacup. According to some estimates, between 2009 and 2013, several Czech universities made around 2 million USD from their researchers their papers and monographs in «predatory» publishing outlets. The case of «predatory» journals was used by some less-productive institutes of the Czech Academy of Sciences to question the system of world's established academic metrics such as Scopus and Web of Science. Conclusions. All this is possible because currently there are many controversial lists and registries of «predatory» journals, which often contradict each other. However, it appears that indexation of academic journals in Scopus and Web of Science databases is more relevant for their academic worthiness than classifying them in accordance to a plethora of various amateurish lists and blogs. Вступ. Публікації в престижних наукових журналах мають суттєвий вплив на рейтинги вищих навчальних закладів та допомагають молодим науковцям отримувати ґранти. Постановка задачі. Академічна гонитва за великою кількістю публікацій призвела до дискусій про феномен так званих «хижих» журналів, які публікують наукове «сміття» за гроші без належного рецензування. Мета. Розкрити сутність «хижих» журналів та довести необхідність індексації як дієвого інструменту оцінки якості наукових публікацій. Матеріали й методи. Використано порівняння рейтингів журналів та наукових публікацій в академічних виданнях та «хижих» журналах. Результати. Чеська Республіка є однією з країн, яка особливо переймається питанням щодо «хижих» журналів. За деякими оцінками, за період 2009—2013 рр. декілька чеських університетів отримали близько 2 мільйонів доларів від публікацій своїх досліджень в газетах та монографіях «хижих» видавництв. Деякі «хижі» журнали використовувалися окремими менш продуктивними інститутами Чеської Академії наук, щоб ставити під сумнів систему світових наукових метрик, таких як Scopus та Web of Science. Висновки. Все це можливо, тому що на сьогодні існує значна кількість списків та реєстрів «хижих» журналів, які часто суперечать один одному. Проте з’ясовується, що індексація академічних журналів у базах даних Scopus та Web of Science більш актуальна для їхньої академічної доброчесності, ніж класифікація їх відповідно до безлічі різних аматорських списків та блогів. Введение. Публикации в престижных научных журналах оказывают значительное влияние на рейтинги высших учебных заведений и помогают молодым ученым получать гранты. Постановка задачи. Академическая гонка за большим количеством публикаций привела к дискуссиям о феномене так называемых «хищных» журналов, публикующих научный «мусор» за деньги без надлежащего рецензирования. Цель. Раскрыть сущность «хищных» журналов и доказать необходимость индексации как действенного инструмента оценки качества научных публикаций. Материалы и методы. Использовано сравнение рейтингов научных журналов и публикаций в академических изданиях и «хищных» журналах. Результаты. Чешская Республика является одной из стран, которая особенно одержима вопросом о «хищных» журналах. По некоторым оценкам, за период 2009—2013 гг. чешские университеты получили около 2 миллионов долларов от публикаций своих исследований в газетах и монографиях «хищных» издательств. Некоторые из «хищных» журналов использовались отдельными менее производительными институтами Чешской Академии наук, чтобы подвергнуть сомнению систему общемировых академических показателей мира, таких как Scopus и Web of Science. Выводы. Все это возможно, потому что в настоящее время существует множество списков и реестров «хищных» журналов, которые часто противоречат друг другу. Однако оказывается, что индексация академических журналов в базах данных Scopus и Web of Science более актуальна для их академической значимости, чем классификация в соответствии с множеством разнообразных любительских списков и блогов.